An analysis of the use of visual elements in workplace diversity disclosure. Issue 2 (19th January 2023) - Momin, Mahmood; Chong, Sabrina
Abstract : Purpose: The purpose of this study is to examine how visual elements along with textual narratives are used to disclose workplace diversity-related information in corporate social and environmental reports. Design/methodology/approach: A qualitative content analysis is used to examine the workplace diversity-related information in the 2016 standalone sustainability/corporate responsibility reports of 47 Fortune companies. A total of 539 tables, figures and photographs and their related textual narratives are analysed through an impression management lens. Findings: The study finds that multiple types of visual elements are used to supplement textual narratives to communicate workplace diversity-related messages. The positive and often non-verifiable workplace diversity-related information is symbolically suggestive of the companies' workplace diversity commitment and success. While tables and figures are typically presented using numbers, percentages and words to enhance and promote the positive information, the "feel-good" photographs are used to arouse positive feelings in the readers. These visual elements are presented in either a single-visual or mixed-visual presentation form. Practical implications: This study has the potential to inform and assist preparers in the use of multiple visual elements and textual narratives to promote an impartial and substantive reporting of workplace diversity-related information. Understanding the motivation behind the usage and presentation of visual elements can be useful for the promulgation of guidelines for workplace diversity disclosure, and make readers aware that the visual elements can be exploited for impression management and symbolic legitimacy. Originality/value: This study provides empirical evidence on the use of multiple types of visual elements in the reporting of workplace diversity-related information. It demonstrates how these visual elements are strategically used and presented to deliver an impression of workplace diversity to the readers.